THE FORMALIZATION OF SHARIA IN ACEH PROVINCE: A GENDER PERSPECTIVE - Teuku Saiful; Indra Kesuma Hadi; Humaira Humaira (Universitas Syiah Kuala, 2023)
This paper explores the dimensions of gender equality within the context of law-making in Aceh province, emphasizing the importance of a gender perspective. Categorized as a normative study, it addresses the current issue by analysing principles, levels of synchronization, legal histories, and comparisons of constitutions. Additionally, an empirical study was conducted, involving interviews with relevant stakeholders directly involved in the development of Aceh Qanun. The findings of this paper highlight that Pancasila, the 1945 Constitution, and CEDAW serve as primary parameters for law-making and the implementation of gender equality in Indonesia. The formalization of shari'a in Aceh province, as a political endeavour by authorities, is seen as crucial for achieving both gender equality and the goals of shari'a (maqasid al-syariah). The inclusion of gender equality in the law-making process, particularly in relation to the implementation of shari'a in Aceh, is a principle that should be comprehensively understood and applied to ensure justice and equality for all genders in the formulation of qanun in Aceh.